A Transient Auditory Signal Shifts the Perceived Offset Position of a Moving Visual Object - Chien, Sung-En; Ono, Fuminori; Watanabe, Katsumi (Frontiers in Psychology, 2013)
Information received from different sensory modalities profoundly influences human perception. For example, changes in the auditory flutter rate induce changes in the apparent flicker rate of a flashing light (Shipley, 1964). In the present study, we investigated whether auditory information would affect the perceived offset position of a moving object. In Experiment 1, a visual object moved toward the center of the computer screen and disappeared abruptly. A transient auditory signal was presented at different times relative to the moment when the object disappeared. The results showed that if the auditory signal was presented before the abrupt offset of the moving object, the perceived final position was shifted backward, implying that the perceived visual offset position was affected by the transient auditory information. In Experiment 2, we presented the transient auditory signal to either the left or the right ear. The results showed that the perceived visual offset shifted backward more strongly when the auditory signal was presented to the same side from which the moving object originated. In Experiment 3, we found that the perceived timing of the visual offset was not affected by the spatial relation between the auditory signal and the visual offset. The present results are interpreted as indicating that an auditory signal may influence the offset position of a moving object through both spatial and temporal processes.